Ionic Liquid Crystals Derived from Amino Acids. Issue 47 (7th October 2013) - Mansueto, Markus; Frey, Wolfgang; Laschat, Sabine
Abstract Novel chiral amino acid derived ionic liquid crystals with amine and amide moieties as spacers between the imidazolium head group and the alkyl chain were synthesised. The key step in the synthesis utilised the relatively uncommon SO3 leaving group in a microwave‐assisted reaction. The mesomorphic properties of the mesogens were determined by differential scanning calorimetry (DSC), polarising optical microscopy (POM) and X‐ray diffraction. All liquid crystalline salts exhibit a smectic A mesophase geometry with strongly interdigitated bilayer structures. An increase of the steric bulk of the stereogenic centre hindered the formation of mesophases. In case of phenylalanine‐derived derivatives a mesomorphic behaviour was observed for shorter alkyl chains as compared to other amino acid derivatives indicating an additional stabilising effect by the phenyl moiety.